THE INTEGRATION OF COMMUNICATIVE LANGUAGE TEACHING (CLT) IN DEVELOPING CRITICAL LISTENING SKILLS (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
This paper explores the integration of Communicative Language Teaching (CLT) in developing critical listening skills among language learners. CLT emphasizes interaction, authentic communication, and learner-centered instruction, making it a suitable framework for fostering higher-order thinking abilities. Through activities such as discussions, debates, and problem-solving tasks, learners engage actively with spoken input, enhancing their ability to analyze, evaluate, and interpret messages critically. The review highlights how CLT-based listening tasks mirror real-life communication, thereby promoting deeper comprehension and critical engagement. Despite challenges in implementation, CLT offers effective strategies to cultivate critical listening skills essential for academic and real-world success.